Succession of Potential Insect and Mite Pests and Known Insect Predators and Parasitoids on Jatropha curcas L. in Andhra Pradesh, India - Satyanarayana, J.; Sudhakar, R.; Sreenivas, G.; Reddy, D. V. V.; Singh, T. V. K. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted at Tree Oils India Limited (TOIL) farm near Zahirabad, Medak District, Andhra Pradesh, India on succession of insect pests of Jatropha curcas L. during January 2010 and December, 2011. Jatropha was infested by an overlapping sequence of 18 insect species. Out of these, the leaf webber, Salebria morosalis (Saalm Uller); bugs, Chrysocoris purpureus (Westw.) and Scutelleria nobilis (Fabricius); papaya mealy bug, Paracoccus marginatus Williams and Granara de Willink and stem girdler, Sthenias grisator (Fabricius) occurred right through the crop growth from their first appearance and were, therefore, designated as ‘major’ pests. A group of predatory coccinellids, Brumoides suturalis (Fabricius), Coccinella septempunctata L. and Menochilus sexmaculatus (Fabricius); spiders; green lacewing, Chrysopa scelestes Banks; black ant; wasps, Polystes hebreaus Fabricius and Vespa orientalis L.; and parasitoid, Acerophagous papaya (Noyes and Schauff) were principal biotic agents found.